Mirrors of the economy national accounts and international norms in Russia and beyond - Herrera, Yoshiko M., 1970-; ebrary, Inc. (Ithaca, N.Y. : Cornell University Press, 2010)
Studies the changeover in postcommunist societies from the Material Product System of accounting to the System of National Accounts system in the early 1990s and adherence to the SNA norms thereafter by means of interviews with Russian statisticians and examination of the in-house journal of Goskomstat (Vestnik statistiki, which became Voprosy statistiki).
A system of national accounts : the postcommunist transformation of Russian statistics -- Accounting for implementation : a theory of conditional norms -- Accidental hegemony : how the system of national accounts became an international norm -- Efficiency, resources, and capacity in the implementation of the SNA -- Cui bono? : politicians, statisticians, and international organizations in Russian implementation of the SNA -- Professionals in the service of the state : the organizational identity of Russian statisticians -- Statistics as a mirror of the economy : the SNA as a conditional norm.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: x; National income -- Russia (Federation) -- Accounting; Russia (Federation) -- Economic conditions -- 1991- -- Statistics; Electronic books